2006
DOI: 10.1128/jb.188.7.2533-2542.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Three Strains of Ehrlichia ruminantium Reveals an Active Process of Genome Size Plasticity

Abstract: Ehrlichia ruminantium is the causative agent of heartwater, a major tick-borne disease of livestock in Africa that has been introduced in the Caribbean and is threatening to emerge and spread on the American mainland. We sequenced the complete genomes of two strains of E. ruminantium of differing phenotypes, strains Gardel (Erga; 1,499,920 bp), from the island of Guadeloupe, and Welgevonden (Erwe; 1,512,977 bp), originating in South Africa and maintained in Guadeloupe in a different cell environment. Comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
91
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 67 publications
6
91
0
Order By: Relevance
“…Indeed, the duplicationloss model suggests that the background frequency of tandem duplications is high, but that the copy number is normally kept in balance by an equally rapid collapse unless there is selection for more than one copy (36,37). Speaking against such a scenario is that the tra clusters are not situated in tandem, that there are few tandem gene repeats inside the clusters, and that the sizes of the repeated clusters is Ͼ10-fold longer than normally found for tandem repeats, such as for example in E. ruminantium (38,39). Furthermore, subsequent intragenomic recombination events must be invoked to explain the current distribution of the tra clusters across the genome.…”
Section: Expansion Of Genes For Conjugative Type IV Secretion Systemsmentioning
confidence: 99%
“…Indeed, the duplicationloss model suggests that the background frequency of tandem duplications is high, but that the copy number is normally kept in balance by an equally rapid collapse unless there is selection for more than one copy (36,37). Speaking against such a scenario is that the tra clusters are not situated in tandem, that there are few tandem gene repeats inside the clusters, and that the sizes of the repeated clusters is Ͼ10-fold longer than normally found for tandem repeats, such as for example in E. ruminantium (38,39). Furthermore, subsequent intragenomic recombination events must be invoked to explain the current distribution of the tra clusters across the genome.…”
Section: Expansion Of Genes For Conjugative Type IV Secretion Systemsmentioning
confidence: 99%
“…Interestingly, the VLPT ortholog that we identified in E. canis in this study lacks the tandem repeats found in the E. chaffeensis VLPT gene, but it has a Ser/Thr/Glu-rich patch that is similar in size and composition to that of a single VLPT repeat unit. The addition and deletion of tandem repeats are considered a major source of change and instability in ehrlichial genomes (11). The fact that the E. canis gp19 protein lacks tandem repeats while the E. chaffeensis VLPT protein has variable numbers is indicative of these genes being affected by this process.…”
Section: Vol 75 2007mentioning
confidence: 99%
“…The genomes of E. canis and other organisms in the genus, including Ehrlichia chaffeensis and Ehrlichia ruminantium, exhibit a high degree of genomic synteny, paralogous protein families, a large proportion of proteins with transmembrane helices and/or signal sequences, tandem repeats and ankyrin domains in proteins associated with host-pathogen interactions, and a unique serine-threonine bias associated with a potential for O glycosylation and phosphorylation (6,10,11,18). A small subset of the approximately 1,000 proteins (including hypothetical proteins) encoded by each of these genomes is recognized by antibody (8,20,25,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, differences also emerge relating to host pathology, the presence or absence of transovarial transmission and adaptation to a haematophagous vector [3], as well as the expansion of families of immunodominant outer membrane proteins, facilitating antigenic variation. The generation of multiple E. ruminantium genome sequences has enabled a third series of comparative approaches [4,5] (Frutos et al, this issue) to understanding the active process of genome evolution.…”
mentioning
confidence: 99%